An Empirical Analysis of Private Equity Investment Affecting Enterprise Value - Li, Jianhong (Université de Genève, 2020)
The lack of long-term and stable financial support for SMEs is the fundamental reason why enterprises cannot develop for a long time. At present, the situation of financing difficulties for SMEs is becoming more and more serious. Private equity (PE) investment has emerged as an important financing method. Private equity investment, while broadening the financing channels of SME capital markets, brings advanced management experience to enterprises, which helps enterprises to develop rapidly and effectively. According to the statistics of the Zero2IPO Research Center, the active investment institutions in China's equity market have grown from more than 200 in 2000 to more than 14,000 in 2018, with a total asset under management over RMB 9 trillion. Great progress has been realized in the scale and development of the industry. In addition, with the launch of the GEM in 2009, PE investment industry met new opportunities of development and became popular. At present, the development of China's PE investment business is still at an early stage. Neither relevant policies, laws and regulations nor supporting mechanisms are mature enough. Therefore, researches on China's PE investment business needs to be carried out. In this context, more and more scholars are beginning to focus on the field of PE investment. This paper focuses on whether PE investments can fundamentally increase the enterprise value. The basic theory is sorted out to serve as the theoretical basis for this study. Through a systematic analysis, this paper draws out 4paths of PE investment affecting enterprises, which are the influence on technological innovation, corporate governance activities, dividend distribution decision and earnings management, respectively. And through empirical analysis, it finds the empirical basis of the impact of PE investment on enterprise value, and investigates how PE investments affect enterprise value based on the difference in investment characteristics such as investment duration and whether the investment is joint or not. This paper conducts an empirical test by selecting the listed companies of the Shenzhen Stock Exchange GEM in 2015-2018 as sample. The results show that the investment of PE firm will significantly increase the value of the target enterprise. This paper makes a detailed analysis of sample data. The conclusion of the study is that private equity investment will have a significant impact on the value of target enterprises. Private equity investment plays an important role in the modern governance structure of small and medium-sized enterprises in China This paper enriches the existing literature and provides constructive suggestions for the health development of the PE investment market. 中小企业缺乏长期稳定的资金来源是企业无法长久发展的根本性原因，目前 中小企业融资难的形势越来越严峻，私募股权投资作为一种重要的融资手段应运 而生。私募股权投资在拓宽中小企业资本市场融资渠道的同时，给企业带来先进的 管理经验，有助于企业快速并有效的发展。据清科研究中心的统计数据显示，中国 股权市场活跃的投资机构已由 2000 年的 200 多家发展到 2018 年的 1.4 万多家，管 理资本量超过 9 万亿人民币，行业规模和发展实现了质的飞跃。此外，随着 2009 年创业板的推出，私募股权投资行业的发展业迎来了新的希望和契机，私募股权投 资业务开始盛行。目前，我国私募股权投资业务的发展还处于早期阶段，无论是从 政策还是法律法规再到配套机制，都还不够健全。因此，对我国私募股权投资业务 的研究亟需开展，在此背景下，越来越多的学者开始关注私募股权投资这一领域。 本文研究的重点是私募股权投资是否能够根本上提升企业价值。本文首先对 基础理论进行了梳理，以此作为研究的理论依据，而后论述了私募股权投资对被投 资企业价值影响的理论分析，。本文通过系统的理论分析得出了私募股权投资影响 企业的路径，并通过实证分析，得到私募股权投资对企业价值的影响的实证依据， 并且从投资期限和是否联合投资等投资特征的差异性，深入研究私募股权投资对 企业价值的影响方式。本文通过选取深圳证券交易所创业板 2015-2018 年的上市企 业作为样本，进行了实证检验，并得出以下研究结论:私募股权投资的参与会显著 提升目标企业的价值，同时，私募股权投资的期限越长、联合投资机构的数量越多， 目标企业的价值也会越高。 本文基于理论又结合实际，对样本数据进行了分析，研究的结论是私募股权投 资会对被投资企业的价值产生显著影响。私募股权投资对于我国中小企业的现代 化治理结构起到了完善作用。本文的研究结果丰富了现有文献，对私募股权投资市 场健康发展提出了建设性的建议。
Keywords: Enterprise Value; Investment Term; PE Investment